2006
DOI: 10.1074/jbc.c600001200
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor-α Binds p53 Tumor Suppressor Protein Directly and Represses Its Function

Abstract: Estrogen receptor-␣ (ER␣) promotes proliferation of breast cancer cells, whereas tumor suppressor protein p53 impedes proliferation of cells with genomic damage. Whether there is a direct link between these two antagonistic pathways has remained unclear. Here we report that ER␣ binds directly to p53 and represses its function. The activation function-2 (AF-2) domain of ER␣ and the C-terminal regulatory domain of p53 are necessary for the interaction. Knocking down p53 and ER␣ by small interfering RNA elicits o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
154
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(159 citation statements)
references
References 31 publications
5
154
0
Order By: Relevance
“…Therefore, other molecular changes that result from BMS and LMS manipulations may have the potential to affect p53 activity and influence cancer risk. For example, ERα protein, which was significantly upregulated in LMS mice, has been shown to suppress p53-mediated transcriptional activity (42,43). Although alterations in p53 protein expression may not be an early step in cancer predisposition or initiation in this model, alterations in the expression or activity of this protein could be a later consequence of other neoplastic changes in the mammary gland induced by early-life stress.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, other molecular changes that result from BMS and LMS manipulations may have the potential to affect p53 activity and influence cancer risk. For example, ERα protein, which was significantly upregulated in LMS mice, has been shown to suppress p53-mediated transcriptional activity (42,43). Although alterations in p53 protein expression may not be an early step in cancer predisposition or initiation in this model, alterations in the expression or activity of this protein could be a later consequence of other neoplastic changes in the mammary gland induced by early-life stress.…”
Section: Discussionmentioning
confidence: 99%
“…ERa binds directly to p53 and represses its function Liu et al, 2006). p53 and ERa dimers interfere with the ability of ERa to bind EREs and thereby inhibit ERa-dependent transcription Yu et al, 1997).…”
Section: Klf4 Suppresses Estrogen-dependent Breast Cancer K Akaogi Et Almentioning
confidence: 99%
“…A recent study by Liu et al found that ESR-α plays an important role in regulating p53 activity. ESR-α binding to p53 leading to functional inactivity of wild-type p53 could be one reason for the inability of wild-type p53 to inhibit tumor growth and metastasis in ESR-positive breast cancer (Liu et al, 2006). Thus, genetic variations in genes controlling estrogen activity, including ESR-α, could reveal a potential risk for breast cancer.…”
Section: Introductionmentioning
confidence: 99%